How to be a bawse : a guide to conquering life - Singh, Lilly, 1988- (New York : Ballantine Books, 2017)
"From the 2017 People's Choice Award winner for Favorite YouTube Star comes the definitive guide to being a bawse: a person who exudes confidence, hustles relentlessly, and smiles genuinely because he or she has fought through it all and made it out the other side. Lilly Singh isn't just a superstar. She's Superwoman--which is also the name of her wildly popular YouTube channel. Funny, smart, and insightful, the actress and comedian covers topics ranging from relationships to career choices to everyday annoyances. It's no wonder she's garnered more than a billion views. But Lilly didn't get to the top by being lucky--she had to work for it. Hard. Now Lilly wants to share the lessons she learned while taking the world by storm, and the tools she used to do it. How to Be a Bawse is the definitive guide to conquering life. Make no mistake, there are no shortcuts to success, personal or professional. World domination requires real effort, dedication, and determination.Just consider Lilly a personal trainer for your life--with fifty rules to get you in the game, including Let Go of FOMO (Fear of Missing Out): Temptation will try to steer you away from your goals. FOMO is just a test of your priorities, a test that a bawse is ready to pass. Be Nice to People: Treat niceness like an item on your daily to-do list. People will go out of their way to help and support you because you make them feel good. Schedule Inspiration: Lack of motivation isn't permanent or a sign of weakness. Expect it and proactively schedule time to be creative. Be the Dumbest: Challenge yourself by surrounding yourself with people who know more than you do. It's a vital way to learn and improve. Told in Lilly's hilarious, bold voice and packed with photos and candid stories from her journey to the top, How to Be a Bawse will make you love your life and yourself--even more than you love Beyonce. (Yes, we said it!) WARNING: This book does not include hopeful thoughts, lucky charms, or cute quotes. That's because success, happiness, and everything else you want in life need to be worked for, not wished for. In Lilly's world, there are no escalators, only stairs. Get ready to climb. Advance praise for How to Be a Bawse "Lilly is a bona fide #girlboss, boss, and bawse. Her meteoric rise has come with so many incredible lessons that we are all lucky to have access to. This book is a must-have for the hustler in all of us."--Sophia Amoruso, founder and CEO, Girlboss"--
Keywords: Singh, Lilly, -- 1988-; Personal Memoirs